2018
DOI: 10.1038/s41467-018-04880-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes associated with cortical malformation using a transposon-mediated somatic mutagenesis screen in mice

Abstract: Mutations in genes involved in the production, migration, or differentiation of cortical neurons often lead to malformations of cortical development (MCDs). However, many genetic mutations involved in MCD pathogenesis remain unidentified. Here we developed a genetic screening paradigm based on transposon-mediated somatic mutagenesis by in utero electroporation and the inability of mutant neuronal precursors to migrate to the cortex and identified 33 candidate MCD genes. Consistent with the screen, several gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 65 publications
3
29
0
Order By: Relevance
“…In addition, a recent transposon-mediated mutagenesis screen using in utero electroporation of mouse embryos to detect mutant neural progenitor (radial glia) cells unable to migrate to the cortex identified 33 candidate genes for malformations of cortical development, one of which was Macf1. 20 Defects in axonal extension and guidance have also been seen with mutations in Short stop (shot), the Drosphila MACF1 homolog that interacts with Robo and Slit and regulates midline axon crossing. 21 In shot mutants, axonal growth cones initiate at the normal time and have normal morphology, including normal axon orientation and fasciculation.…”
Section: Mouse Knockoutsmentioning
confidence: 99%
“…In addition, a recent transposon-mediated mutagenesis screen using in utero electroporation of mouse embryos to detect mutant neural progenitor (radial glia) cells unable to migrate to the cortex identified 33 candidate genes for malformations of cortical development, one of which was Macf1. 20 Defects in axonal extension and guidance have also been seen with mutations in Short stop (shot), the Drosphila MACF1 homolog that interacts with Robo and Slit and regulates midline axon crossing. 21 In shot mutants, axonal growth cones initiate at the normal time and have normal morphology, including normal axon orientation and fasciculation.…”
Section: Mouse Knockoutsmentioning
confidence: 99%
“…These experiments revealed that the PB-based IUE method provides a valuable new tool for tracking and manipulating neural lineages. Recently, Lu et al [39] applied IUE coupled with PB-mediated somatic mutagenesis to identify potential genes involved in the behavior of cortical neurons in the developing neocortex that often lead to malformations of cortical development (MCDs). IUE was performed at Day 14.5 of the embryonic stage, at the time when cortical neurogenesis is known to be most active.…”
Section: In Utero Gene Deliverymentioning
confidence: 99%
“…The maximum cargo size of viral vectors is restricted, hampering gene delivery of larger genes. Furthermore, construction of viral vectors is time-consuming, costly, and requires living cells for their large-scale production, which is also gene-wide screening of genes related to neural development and disorders [39]. PB is also known for its importance in inducing immortalization of cultured human deciduous tooth dental pulp cells [40] and hepatocytes in vivo [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seminal studies have taken advantage of retroviral vectors to characterize the neuronal and glial descent of embryonic neural progenitors in model animals (Noctor et al, 2001;Price et al, 1987;Yu et al, 2012). The location of these progenitors along the lumen of the neural tube also makes them accessible to integrative schemes based on DNA electroporation applicable to trace neural cell lineage (Chen and Loturco, 2012;Loulier et al, 2014), target specific genes and mark their product (Mikuni et al, 2016;Suzuki et al, 2016), or even perform in situ screens for genes involved in neurodevelopmental processes (Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%